Removal of Methyl Orange Dye from Aqueous Solution onto Sustainable Sugarcane Bagasse (Gramineae Saccharum) Biomass - Daroies, Suhada; A. Hamid, Hazren (Progress in Engineering Application and Technology, 2024)
An investigation into the effectiveness of sustainable sugarcane bagasse as an adsorbent for the removal of methyl orange dye from aqueous solutions is being carried out in this work. Experiments involving batch adsorption were carried out in order to determine the influence that certain parameters can have on the removal efficiency. These parameters included initial dye concentration, sorbent dosage and contact time. According to the findings, sugarcane bagasse has the potential to be an efficient adsorbent for methyl orange dye, demonstrating a capacity for adsorption that may be considered favourable. A sustainable approach to alleviate water pollution caused by dye effluents was offered by the procedure, which indicated promising potential for application in wastewater treatment. The adsorption data from the batch experiments were evaluated using the Langmuir and Freundlich adsorption isotherms and pseudo 1st and 2nd order kinetic models. The optimal parameter has been determined to be the sorbent dosage of 6g, with the dye concentration being between 237 and 388 ADMI, and the contact time being 120 minutes. The application has demonstrated satisfactory absorption which means that the water meets the required quality standards A for industrial effluent to be discharged into the river. It is possible that the practical usability and sustainability of this approach in real-world circumstances could be improved by further optimisation and research of regeneration approaches.